"'Real Men' Support Their Wives": Reconstructing Masculinity Among Men in Rural Northwestern Ghana. (2021) - Dery, Isaac; Akurugu, Constance Awinpoka
Abstract: Although there is growing debate among feminist scholars on how fathers often socialize their male children to aspire to embody specific values and behaviors, there is limited academic research on how fathers themselves construct and represent masculinity in Ghana. This article draws on data from six focus group discussions held with forty men to foreground men's negotiations, expressions, and representations of masculinity among the Dagaaba in northwestern Ghana. Our findings suggest that men in rural northwestern Ghana are likely to embody hybrid masculinities where traditionally hegemonic masculine ideals—such as men being seen as independent breadwinners—and contemporary gender-conscious norms—such as men as supportive partners—interact in complex ways. Yet the hybridization of masculinity both challenges and reinforces patriarchal gender arrangements in subtle ways. By maintaining a keen interest in their heteronormative breadwinning role as a model of masculinity, educated and gainfully employed men are critical of patriarchal norms that may be destructive to feminist discourses, yet their representations of masculinity indirectly embolden male hegemony in marriage relationships. Our findings further reveal considerable ambiguity in how men define themselves as supportive allies of feminist discourses by endorsing gender egalitarianism, yet none of them visibly challenges why women cannot also be breadwinners.